Validation of Method for Determining Alpha- Mangostin Level of Ethyl Acetate Extract of Mangosteen Rind Using TLCSpectrodensitometry - N. P. A. D. Wijayanti; L.P.M.K. Dewi; K.W. Astuti (Journal of Health Sciences and Medicine, 2017)
Abstract Objective: Mangosteen rind (Garcinia mangostana L.) contains secondary metabolites, namely alpha-mangostin which has antioxidant activity, as well as antibacterial and anti-aging properties. In order to obtain a maximum amount of alpha-mangostin compounds, the maceration method using ethyl acetate was used. To ensure the effectiveness of the mangosteen rind extraction process, all of the processes and methods in preparing the extract should be properly controlled, particularly the analytical method used in determining the alpha-mangostin level of the extract. The method used should be able to determine the alphamangosteen level accurately. This study aimed to test the validation of the analytical method used. Method: The parameters for the validation of the analytical method tested in this study include accuracy, precision, range and linearity, limit of detection (LOD), limit of quantitation (LOQ) and specificity. In this study, the level of alpha-mangostin in the extract was determined using TLC-Spectrodensitometry with the stationary phase of the silica gel plate GF 254 and the mobile phase of chloroform and methanol (10:0.1 v/v). Result: The results of the study showed that this method has met the acceptance criteria for validation with the accuracy value in the range of percent recovery, from 93.85 % to 111.16%; precision with KV <2%; specification with spectrum correlation >0.99; linearity with r =0,99372; limit of detection (LOD) of 5.33 ng and limit of quantitation (LOQ) of 11.43 ng.